Italian Americans - Aldridge, Rebecca (Philadelphia : Chelsea House Publishers, 2003)
Discusses the immigration of Italians to America, including their reasons for leaving Italy, where they settled, the obstacles they faced, and the contibutions they brought to America.
An overview -- The old country -- The journey -- Starting a new life -- Settling in America -- Putting down roots.
Includes bibliographical references (p. 106-107) and index.
Keywords: Italian Americans; Italian Americans -- History; Immigrants